2021
DOI: 10.2196/24374
|View full text |Cite
|
Sign up to set email alerts
|

Shaping Workflows in Digital and Remote Diabetes Care During the COVID-19 Pandemic via Service Design: Prospective, Longitudinal, Open-label Feasibility Trial

Abstract: Background The COVID-19 pandemic poses new challenges to health care providers and the delivery of continuous care. Although many diabetes technologies, such as insulin pumps and continuous glucose monitors, have been established, the data from these devices are rarely assessed. Furthermore, telemedicine has not been sufficiently integrated into clinical workflows. Objective We sought to remotely support children with type 1 diabetes and their caregiver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 65 publications
(78 reference statements)
0
29
0
4
Order By: Relevance
“…Self-care has proven to be a robust tool in times of the COVID-19 pandemic. Important diseases such as diabetes [20] or cardiac diseases [21] benefit greatly from mHealth initiatives that rely on self-care and remote monitoring.…”
Section: Why the Need Of A Study On The Digital Dividementioning
confidence: 99%
“…Self-care has proven to be a robust tool in times of the COVID-19 pandemic. Important diseases such as diabetes [20] or cardiac diseases [21] benefit greatly from mHealth initiatives that rely on self-care and remote monitoring.…”
Section: Why the Need Of A Study On The Digital Dividementioning
confidence: 99%
“…Most of the studies included did not include a formal telemedicine component, rather they collected data from an observational standpoint and made no assessment of the nature of telemedicine contacts between patients and their diabetes HCPs, although these are acknowledged to have happened. However, 4/27 studies did involve an active telemedicine intervention and in each of these studies [23][24][25][26] there was an improvement in glucose metrics. Most tellingly, in the study by Alharthi [26], CGM users were categorized into two groups, one that participated in a single telemedicine consult during the 6-week lockdown study period (n = 61) and one that did not (n = 40).…”
Section: Time In Range During Covid-19mentioning
confidence: 99%
“…In doing so, the most agile services have emphasised and adopted systems and technologies that support people with diabetes in new models of care that minimise their need to attend busy medical centres. It is not a coincidence that the early adopters of new service designs are paediatric diabetes clinics [9,23,70], one of which reports more than 80% of scheduled visits had been accomplished by telemedicine within 3 weeks of starting, with fewer missed appointments [70].…”
Section: Diabetes Services Already Employ Tools Needed For Telemedicine and Telemonitoringmentioning
confidence: 99%
“…However, the concept has most effectively been validated by a successful switch to telemedicine during COVID-19, in which one clinic reported that > 80% of scheduled visits were accomplished by telemedicine [ 38 ], with fewer missed appointments. A separate prospective study of a COVID-safe paediatric telemedicine workflow [ 39 ] found that %TIR and percent time above range (%TAR) significantly improved in children with T1DM, whilst percent time below range (%TBR) did not change, and that psychosocial health improved after 6 months.…”
Section: The Reality Of Telemedicine Telemonitoring and Mhealth In Diabetesmentioning
confidence: 99%